Phenotyping GABA transaminase deficiency: a case description and literature review. Issue 5 (4th July 2016) - Louro, Pedro; Ramos, Lina; Robalo, Conceição; Cancelinha, Cândida; Dinis, Alexandra; Veiga, Ricardo; Pina, Raquel; Rebelo, Olinda; Pop, Ana; Diogo, Luísa; Salomons, Gajja S.; Garcia, Paula
Abstract: Gamma‐aminobutyric acid transaminase (GABA‐T) deficiency is an autosomal recessive disorder reported in only three unrelated families. It is caused by mutations in the ABAT gene, which encodes 4‐aminobutyrate transaminase, an enzyme of GABA catabolism and mitochondrial nucleoside salvage. We report the case of a boy, deceased at 12 months of age, with early‐onset epileptic encephalopathy, severe psychomotor retardation, hypotonia, lower‐limb hyporeflexia, central hypoventilation, and rapid increase in weight and, to a lesser rate, length and head circumference. He presented signs of premature pubarche, thermal instability, and water–electrolyte imbalance. Serum total testosterone was elevated (43.3 ng/dl; normal range <16), as well as serum growth hormone (7.7 ng/ml; normal range <1). Brain magnetic resonance imaging (MRI) showed decreased myelination and generalized brain atrophy, later confirmed by post‐mortem examination. ABAT gene sequencing was performed post‐mortem, identifying a homozygous variant c.888G > T (p.Gln296His), not previously described. In vitro analysis concluded that this variant is pathogenic. The clinical features of this patient are similar to those reported so far in GABA‐T deficiency. However, distinct mutations may have a different effect on enzymatic activity, which potentially could lead to a variable clinical outcome. Clinical investigation aiming for a diagnosis should not end with the patient's death, as it may allow a more precise genetic counselling for the family.